Factors Influencing Sustainable Economic Empowerment of Small-Scale Women Entrepreneurs Using a Local Government Women’s Development Fund in Tanzania - D.Ngoyo, Laurent; E.Lubuva, Elisei; Lupala, Furaha (Local Administration Journal, 2023)
The study assessed factors influencing sustainable empowerment of women small-scale entrepreneurs using the Women’s Development Fund (WDF). It adopted the elements and factors for a sustainability framework to examine the contribution of WDF to women small-scale entrepreneurs’ beneficiary groups. Qualitative and quantitative methods were used in a cross-sectional design to collect data meriting a complementary understanding of the study problem. Findings revealed low business performance among beneficiary groups due to gaps in the 4% allocation from Local Government Authorities (LGAs) for loans, delay of loan disbursement, inadequate entrepreneurship training to beneficiary groups, and limited supportive supervision to credit beneficiaries. Moreover, their business performance has also been affected by limited entrepreneurship capability and non-compliance with WDF guidelines, which increased loan defaults. This paper recommends a study to compare business performance between WDF groups with loans from other Microfinance Institutions (MFIs) for enhancing LGAs’ management of empowerment programs.